การเกิดโรคข้อเข่าเสื่อมในสุนัขที่เป็นโรคสะบ้าเคลื่อน - บุรินทร์ บุญศรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Patellar luxations contribute to cartilage erosion which can be developing to cartilage degradation. This research divided to 2 studies. The objectives of the first study were to prevalence of cartilage erosion in dogs with patellar luxation and relation between cartilage erosion and severity of patellar luxation. Sixty dogs with patellar luxation, 48.65% was grade III patellar luxation and 35.14 was grade IV patellar luxation. There was a relation between cartilage erosion and severity of patellar luxation. In second study, the objective was to study of gene expression of osteoarthritis in articular cartilage from dogs with patellar luxation. 34 dogs divided into 4 groups, group 1 was dogs with normal articular cartilage (Nor) (n=5), group 2 stifle osteoarthritic dogs (OA) (n=13), group 3 was dogs with patellar luxation and not found cartilage erosion (PL) (n=6), and group 4 was dogs with patellar luxation and found cartilage erosion (PLCE) (n=10). HAS-1, HAS-2, COL2A1, MMP-3, IL-1, AGG-1 and TIMP-1 were perform in the study by real-time PCR. The results was found expression of HAS-1, COL2A1, MMP-3, IL-1β, AGG in PL and PLCE different from Nor (P<0.05) In conclusion, patellar luxation contribute the cartilage erosion and one cause of stifle osteoarthritis. The management of stifle osteoarthritis must be considered in treatment of patellar luxation. Moreover, early treatment of patellar luxation may be preventing stifle osteoarthritis.